Is there an association between superoxide dismutase gene polymorphisms, antioxidants in oxidative stress pathway, and oral health-related quality of life after root canal treatment? - Ludmila da Silva Guimarães; Erlange Andrade Borges da Silva; Juliana Miranda Bonelli; Heitor Ganier Ribeiro; Alice Corrêa Silva-Sousa; Manoel Damião Sousa-Neto; Erika Calvano Küchler; Lívia Azeredo Alves Antunes; Fernanda Signorelli Calazans; Leonardo Santos Antunes (Acta Odontologica Scandinavica)
Objective: To evaluate the association between genetic polymorphisms in SOD2 and SOD3 and oral health-related quality of life (OHRQoL).